“Too Wet, Too Steep, and Covered with Shifting, Unstable Sand”: Sable Island and Anti-submarine Warfare During the 20th Century - Coombs, Adam (The Northern Mariner / Le marin du nord)

(untitled) (Canadian Nautical Research Society and North American Society for Oceanic History, 2025)
Sable Island is best known for its shipwrecks and ponies. Additionally, it has an unexplored place in the history of Canadian anti-submarine warfare in the Atlantic. This paper examines how the Royal Canadian Air Force and Royal Canadian Navy used and sought to use Sable Island in their anti-submarine warfare operations throughout the Second World War (1939–45) and the early Cold War (1947–68). It argues that while Sable Island’s location made it an ideal base for submarine hunting aircraft, the harsh environment and challenges of building on a sandbar in the Atlantic Ocean limited its utility for Canada’s air force and navy.